Peningkaan UKM Produk Pangan Olahan Ikan terhadap Keamanan Pangan di Kecamatan Mayangan Kota Probolinggo - Abrina Anggraini, Sinar Perbawani ; Boedirohminarni, Arfida ; Wachid, Mochammad (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
The activities will be done in subdistrict Mayangan Probolinggo which is one of the priorityprogrammes of the medium-term development plan of Probolinggo. The potential of localresources need to be developed through the development of the UKM community subdistrictMayangan with an increase of processed fish products, problems that need to be examined arethe limited employment opportunities, lack of skills, as well as the low level of entrepreneurialsoul, most of the fisherman is fishing with traditional socio-cultural characteristic that are notyet conducive to the progress of the efforts, has not been optimal the efforts of the utilization ofpotential resources, and the decrease in the quality and quantity of processed products of localresources. The aim of activities is the entrepreneurial increase of fishing communities throughthe formation of business community and community management efforts through the processedproduct quality control technique based on local resources in particular processed fish. See theurgency of the problems that exist, then in this activity for the increase of the entrepreneurialcommunity through the establishment of Mayangan subdistrict community effort of thecommunity of processed products based on resources locally processed fish, in particular theextension of knowledge entrepreneurship to increase prosperity which is based on principles ofsustainability and local development embody empowerment resource potential of the localsubdistrict of Mayangan. The methods that will be used through outreach, training andmentoring direct to the public subdistrict Mayangan to the increase of the entrepreneurialcommunity.